Spatial clusters and temporal trends of groundwater storage in the Paranapanema River Basin, Brazil - Manzione, Rodrigo Lilla [UNESP]; Brizotti, Carolina Souza [UNESP] (Elsevier, 2025)
The Paranapanema River Basin (PRB) is a hydroelectrical and agricultural hub situated the southeast part of Brazil. From 2018 to 2022, a water crisis due precipitation much below the average in this hydrographic region boost a run for groundwater. It resulted in indiscriminate drilling of clandestine wells all over the basin without considering how the diminishing amounts of precipitation were affecting groundwater storage (GWS). This study used GWS satellite-based estimatives and exploratory spatial and temporal data analysis (ESTDA) to verify the presence of spatial cluster and temporal trends in the groundwater reserves of the PRB. Hot spots (spatial clusters of high values) were detected in the southeastern heads of the basin and cold spots (spatial clusters of low values) were found in the western portion of the basin, near the outlet. The time series trends detected in the dataset were not statistically significant. Although, two classes of hot spots were observed (persistent and intensifying) as well three classes of cold spots (persistent, diminishing, and sporadic). The information about where the large reserves are concentrated and how the storage changes over time increase the perception of water managers and decision makers about the potential of groundwater and the consequences of climate and human disturbances in the groundwater regime. Groundwater managements can benefit of spatial and temporal distribution of groundwater reserves to plan future exploitation, legislation, regulation and consequently increase the governance about this important natural resource.